(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
In this article, I have sought to demonstrate the existence—within the discourse of Melchisedec Ştefănescu—of an implicit representation of an axiological "center" that grants the author a privileged position. This *locus* is situated at the intersection of two axes, which combine national and confessional markers. Just as the resulting scale of values ​​does, the associated geographical and social connotations serve to place the author at the center. This position, assigned to the bishop as a participant in the symbiosis of Orthodoxy and "Romanianism," relies on the symbolic marginalization or exclusion of those who differ in national or confessional terms. Thus, the positive valuation of "us" (or "me") occurs in direct relation to the attribution of negative characteristics to—or the devaluation of—"the others." In this context, "the others" comprise non-Orthodox individuals and non-Romanians—specifically Catholics, Protestants, Lipovans (adherents of schismatic movements within Russian Orthodoxy), Jews, and Muslims, as well as Russians, Bulgarians, Armenians, and Roma. The disparagement of the Other arises from the distance relative to the center—a distance determined by the degree of divergence from the center's attributes. The expansion of the center toward the periphery remains an imperative that encompasses the entire periphery, yet its significance varies according to the aforementioned distance. Generally, the tendency for such expansion is inversely proportional to the disdain shown toward the Other; consequently, the focus shifts from emphasizing assimilation strategies to highlighting manifestations of exclusion.